2019
DOI: 10.1097/sla.0000000000003703
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary Mucinous Neoplasms: Have IAP Consensus Guidelines Changed our Approach?

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The management of IPMN has continuously been in the focus of scientific debate, and international guidelines have repeatedly been revised over the last years [1,44,46]. Improvements in image quality and increasing number of imaging examinations contribute to higher detection rates of IPMN, which consequently resulted in growing numbers of IPMN resections [5,20,47]. At the same time, the limited diagnostic accuracy of current diagnostic modalities for the identification of HGD or invasive cancer in IPMN, that defines further therapeutic management, has been recognized [5,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management of IPMN has continuously been in the focus of scientific debate, and international guidelines have repeatedly been revised over the last years [1,44,46]. Improvements in image quality and increasing number of imaging examinations contribute to higher detection rates of IPMN, which consequently resulted in growing numbers of IPMN resections [5,20,47]. At the same time, the limited diagnostic accuracy of current diagnostic modalities for the identification of HGD or invasive cancer in IPMN, that defines further therapeutic management, has been recognized [5,47].…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in image quality and increasing number of imaging examinations contribute to higher detection rates of IPMN, which consequently resulted in growing numbers of IPMN resections [5,20,47]. At the same time, the limited diagnostic accuracy of current diagnostic modalities for the identification of HGD or invasive cancer in IPMN, that defines further therapeutic management, has been recognized [5,47]. Recent multi-center studies indicated a significant inter-institutional variance of diagnostic performance and available studies investigating the accuracy of current guidelines for the detection of HGD and invasive cancer in IPMN point towards a risk for surgical overtreatment in correlation to the histopathological results of malignancy [12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One should consider that most of the malignancy estimates stem from resected series at tertiary centers with some lag time in reporting (and based on institutional practice at the time of resection) and, hence, have a selection bias incurred. 14 Thus, there is a risk for both over-and undertreatment with any management strategy, which needs to be considered by the clinician as well as the patient.…”
Section: Clinical Management Of An Incidental Pancreatic Cystmentioning
confidence: 99%
“…Over the past decades, IPMNs have had an increasing incidence and constitute the largest proportion of pancreatic cystic lesions 2,4 . Incidentally diagnosed IPMNs account for many pancreatic surgeries, but controversy remains since the proportion of malignant IPMNs according to postoperative histology in all resected IPMNs is decreasing 5 . The e cacy of radiological examination is unsatisfactory; therefore, to accurately perform surgical resection on invasive IPMNs while avoiding unnecessary surgery, there is a clinical need to nd sensitive and speci c preoperative indications to assess the necessity of surgery 6 .…”
Section: Introductionmentioning
confidence: 99%